Social and environmental protection in Islamic social enterprise: a proposed model for sustainability - Martoza, Md. Golam; Rosman, Romzie; Syed Jaafar Alhabshi, Syed Musa; Hossain, Mohammad Enayet; Marziya, Fatimatum (Springer, 2024)
The purpose of this qualitative study is to generate a conceptual model for sustainability in Islamic social enterprise organization that explores how Islamic social enterprise organizations tackle the social and environmental challenges in Bangladesh. This is a multiple case study approaches based on descriptive and exploratory research. The interview data were collected from three Islamic social enterprise organizations that employ a semi-structured interview questions using thematic analysis which consists of three overarching themes and six sub-themes. This study has analyzed organizational performance on social and environmental factors. The result shows that the humanitarian strategy among the organizations is essentially the same. In terms of products innovation for poverty alleviation, three organizations have similar perspectives that are limited to financing only and have a lack of innovativeness and sustainability.